2021
DOI: 10.1111/ijd.15755
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil/lymphocyte ratio (NLR) and red blood cell distribution width (RDW) correlate with advanced stages in cutaneous squamous cell carcinoma

Abstract: Background The neutrophil/lymphocyte ratio (NLR) and red blood cell distribution width (RDW) at diagnosis have been shown to correlate with advanced disease and to be prognostic factors in many tumors. However, their role as a prognostic factor for cutaneous squamous cell carcinoma (cSCC) has not yet been studied.Objective Therefore, the aim of our study was to evaluate the correlation of NLR and RDW with stages of disease in patients with cSCC in order to define whether or not higher values of these two marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Among the non-melanoma skin cancers, a retrospective analysis of newly diagnosed cutaneous squamous cell carcinoma patients showed that the median NLR among patients with early stage disease (in situ and stage I) was 2.2, while the median NLR for patients with advanced disease was 4.87. These data demonstrate how high NLRs correlate with higher stages of disease, requiring a strict follow-up and an early treatment for those patients with cutaneous squamous cell carcinoma and a high NLR [50]. Furthermore, in a single-center retrospective case series, Maeda et al, in a previous analysis, analyzed the relationship between the NLR and survival in individuals with squamous cell carcinoma of the skin; furthermore, they studied the correlation between the NLR and sentinel lymph node positivity.…”
Section: Nlr In Cancermentioning
confidence: 64%
See 2 more Smart Citations
“…Among the non-melanoma skin cancers, a retrospective analysis of newly diagnosed cutaneous squamous cell carcinoma patients showed that the median NLR among patients with early stage disease (in situ and stage I) was 2.2, while the median NLR for patients with advanced disease was 4.87. These data demonstrate how high NLRs correlate with higher stages of disease, requiring a strict follow-up and an early treatment for those patients with cutaneous squamous cell carcinoma and a high NLR [50]. Furthermore, in a single-center retrospective case series, Maeda et al, in a previous analysis, analyzed the relationship between the NLR and survival in individuals with squamous cell carcinoma of the skin; furthermore, they studied the correlation between the NLR and sentinel lymph node positivity.…”
Section: Nlr In Cancermentioning
confidence: 64%
“…These findings can be applied also in solid cancers where an elevated NLR is correlated to a dismal prognosis [47][48][49][50]. Recently, some authors have also demonstrated how activated neutrophils can produce the neutrophil extracellular traps (NETs) that are net-like structures composed of DNA-histone complexes and proteins [51].…”
Section: Neutrophilsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a retrospective study with 51 newly diagnosed cSCC patients, Di Raimondo et al [ 43 ] evaluated the correlation of NLR with the stage of the disease. With a median NLR = 2.2, the NLR values were significantly lower in non-advanced disease stages (in situ and stage I), compared to more advanced (stages > I) of cSCC (NLR = 4.87).…”
Section: Resultsmentioning
confidence: 99%
“…PLR, similar to NLR and ELR, is a simple blood biomarker that has previously been linked to systemic inflammation and cancer of many types [ 29 ]. Many studies have shown connections in these biomarkers in MM and cutaneous SCC, yet evidence on BCC is sparse [ 19 , 30 , 31 ]. Inflammation and immunity have commonly been accepted to play a role in carcinogenesis, and these blood biomarkers could serve as a minimally invasive and inexpensive method in skin cancer risk assessment.…”
Section: Discussionmentioning
confidence: 99%